Crescimento de mudas de eucalipto irrigadas com água de diferentes qualidades - Lougon, Marcela Silva (2010)
Agricultural use of water of inferior quality is an option for meeting the water needs together with supply of nutrients to plants, and also provide an appropriate means of disposal of effluents. With this work aimed to evaluate the production of Eucalyptus irrigated with water of different quality standards. We conducted experiment in completely randomized design in factorial 5X3X2 (five evaluation periods, three patterns of water quality and two species of Eucalyptus sp.) With three replications. The waters were used public water supply of the city of Jeronimo Monteiro-ES, aquaculture effluent from the Federal University of Saint Spirit Campus and Alegre effluent treatment system for domestic sewage from the city of Jeronimo Monteiro-ES. The species used were Eucalyptus urophylla and Eucalyptus urograndis. Seedlings were grown in plastic pots with a capacity of 50 cubic centimeters of substrate which were kept in the nursery until the ninety days after sowing submitted to sprinkler irrigation. After that period the tubes containing the seedlings of both species were transferred to polyethylene trays containing three water standards, where we used a system of subirrigation. The tubes were submerged to a depth of 2 cm from its base, absorbing water by capillary action. To evaluate the growth of seedlings of Eucalyptus was made a set of measurements every 20 days, a total of five evaluations started from the transfer of tubes to the trays. In each set of measurements were quantified the height of the shoots, the stem diameter, leaf area, total dry matter of shoots and roots, the leaf area ratio, specific leaf area, the ratio weight of the sheet, the ratio shoot height / neck diameter, the ratio shoot / root, the absolute growth rate, the relative growth rate, the net assimilation rate; Index Dickson quality and efficiency of use water. Was the analysis of different patterns of quality of water used for irrigation, where it was determined pH, potassium, sodium, chloride, iron, phosphorus, ammonia nitrogen, calcium, magnesium, sulfur, electrical conductivity and x sodium adsorption ratio. None of the three standard qualities of water use restrictions as presented to salinity. However, when related to possible problems of water infiltration into the soil, water supply and fish showed a severe degree of restriction and treated wastewater reuse showed a moderate constraint. Regarding the toxicity of irrigation water, the three different types of water, do not set any restrictions and the pH value showed normal, between 6.5 and 8.4. There was also no excess of iron and sulfur in waters with different quality standards considered. The concentration of phosphorus and ammonia nitrogen values were normal for the public water supply and fish, less than 5 mg L-1 for nitrogen and less than 30 mg L-1 for phosphorus. However, for treated wastewater reuse, the levels were above normal values for irrigation. Overall, there was a significant effect on water quality in the growth of Eucalyptus seedlings over the period of measurements, depicted in the superiority of leaf area, total dry matter of shoots and roots, leaf area ratio, area Specific leaf, leaf weight ratio, height ratio of shoot / root collar diameter; shoot ratio and root system of Quality Index Dickson was used when the effluent coming from the sewage treated.